Testing and identification of bovine viral diarrhea virus isolates recovered in Russia between 2019 and 2022 - R. I. Bubyakin; S. V. Kononova; I. N. Shumilova; O. P. Byadovskaya; A. O. Krotova; A. V. Kononov (Ветеринария сегодня)
Studying the agents of bovine viral diarrhea (BVD) is an important task given the high probability of new isolate introduction into the Russian Federation, as well as the need to take into account the genotype and subgenotype of the virus circulating in a herd when developing vaccines and diagnostic kits for the infection. During the work performed, 6 BVD virus isolates were recovered and identiﬁed. The recovery of these isolates in the lamb testicle cell subculture revealed that Bashkiria/2019, Kirov/2020 and Samara/2020 isolates belong to non-cytopathic bovine viral diarrhea virus biotypes, Chelyabinsk/2021 isolate demonstrated the characteristic cytopathic eﬀect in the monolayer and was classiﬁed as a cytopathic variant of thevirus, the adaptation of Belgorod/2021 and Udmurtiya/2020 isolates to this cell system was not possible. The study also identiﬁed the species of the recovered isolates. Based on the analysis of the nucleotide sequence of genome 5’-untranslated region (5’-UTR) fragment, these isolates were classiﬁed as belonging to three genotypes of the virus. The phylogenetic analysis showed that Chelyabinsk/2021 and Udmurtiya/2020 isolates belong togenotype2 and demonstrate, respectively, 98% and99% homology with reference 890 strain of BVD virus. The recovered Bashkiria/2019, Samara/2020, Kirov/2020 isolates were classiﬁed as belonging to subtypes 1i, 1f and1b ofgenotype1, and Belgorod/2021 solate represents genotype 3 of the virus. The ﬁndings from the study conﬁrm the presence of all three genotypes of bovine viral diarrhea virus in the Russian Federation and reiterate the need for the development of speciﬁc prevention and diagnosis tools for the disease.